Fas activation alters tight junction proteins in acute lung injury. Issue 1 (1st November 2018) - Herrero, Raquel; Prados, Lucia; Ferruelo, Antonio; Puig, Ferranda; Pandolfi, Rachele; Guillamat-Prats, Raquel; Moreno, Laura; Matute-Bello, Gustavo; Artigas, Antonio; Esteban, Andres; Lorente, José Ángel
Abstract : Background: The acute respiratory distress syndrome (ARDS) is characterized by protein-rich oedema in the alveolar spaces, a feature in which Fas-mediated apoptosis of the alveolar epithelium has been involved. Objective: To determine whether Fas activation increases protein permeability by mechanisms involving disruption of the paracellular tight junction (TJ) proteins in the pulmonary alveoli. Methods: Protein permeability and the expression of TJ proteins were assessed in vivo in wild-type and Fas-deficient lpr mice 16 hours after the intratracheal instillation of recombinant human soluble Fas ligand (rh-sFasL), and at different time points in vitro in human pulmonary alveolar epithelial cells (HPAEpiC) exposed to rh-sFasL Results: Activation of the Fas pathway increased protein permeability in mouse lungs and altered the expression of the TJ proteins occludin and zonula occludens-1 in the alveolar–capillary membrane in vivo and in human alveolar epithelial cell monolayers in vitro. Blockade of caspase-3, but not inhibition of tyrosine kinase dependent pathways, prevented the alterations in TJ protein expression and permeability induced by the Fas/FasL system in human alveolar cell monolayers in vitro. We also observed that both the Fas-induced increase of protein permeability and disruption of TJ proteins occurred before cell death could be detected in the cell monolayers in vitro. Conclusion: Targeting caspase pathways could prevent the disruption of TJs and reduce the formation of lung oedema in the early stages of ARDS.